2002
DOI: 10.1123/japa.10.2.169
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and Physical Functions of Older Adults: A Review

Abstract: This review examines the influences of physiological aging processes on connective tissue, joint integrity, flexibility (range of motion [ROM]), and physical functions of older adults. Studies that attempted to improve older adults' ROM are also critiqued. Multiple mechanisms of musculoskeletal and soft-tissue degeneration, as well as disease processes (osteoporosis, arthritis, atherosclerosis), contribute to significant decreases in neuromuscular function and ROM in older adults, all of which can be exacerbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
2
34

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 0 publications
0
52
2
34
Order By: Relevance
“…The aging process involves a series of changes, including the reduction of the physical fitness (Wilmore et al 2010;Janssen et al 1985;Holland et al 2002), mainly of aerobic endurance, strength, and balance. These changes impact the everyday life of older adults, limiting their capacity to accomplish normal activities in a comfortable manner and increasing the risk of falls, which affects their functional independence and quality of life (Power and Howley 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The aging process involves a series of changes, including the reduction of the physical fitness (Wilmore et al 2010;Janssen et al 1985;Holland et al 2002), mainly of aerobic endurance, strength, and balance. These changes impact the everyday life of older adults, limiting their capacity to accomplish normal activities in a comfortable manner and increasing the risk of falls, which affects their functional independence and quality of life (Power and Howley 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the mean flexibility in trunk side-bending deteriorated markedly in all age groups. Phillips and Haskell (1995) and Holland et al (2002) also reported age-related declines in flexibility at the trunk and at several joints (shoulder, hip, knee, angle) with functional importance. According to former cross-sectional findings among the present study sample (Malmberg et al 2002a), poor flexibility in trunk side-bending is associated with poor self-rated mobility function.…”
Section: Walk (S)mentioning
confidence: 93%
“…According to former cross-sectional findings among the present study sample (Malmberg et al 2002a), poor flexibility in trunk side-bending is associated with poor self-rated mobility function. Loss of height (Suominen 1997) due to the degenerative changes and the loss of bone in the spine can cause changes in posture as well as deterioration of spinal flexibility (Holland et al 2002). Both of these can affect postural control.…”
Section: Walk (S)mentioning
confidence: 99%
“…Este último factor puede ser considerado como el mayor limitador de la flexibilidad en el envejecimiento (Holland, Tanaka, Shigematsu y Nakagaichi, 2002), pues el estilo de vida sedentario tan característico en el sujeto mayor es marcado por el desuso de las articulaciones y la falta de estímulos para alongar los músculos. Consecuentemente, eso genera la pérdida de amplitud del movimiento articular, que a su vez puede interferir en la ejecución de tareas sencillas del día a día, como: peinarse, salir y entrar del coche, vestirse y desvestirse, ponerse los calcetines, etc.…”
Section: Introductionunclassified